Stable Isotopes Analysis of Black Lion Tamarins Reveals Increasing Arthropod Consumption When Fruit Productivity Decreases in Forest Fragments - Raskin, Amazone; Kaisin, Olivier [UNESP]; Michel, Loïc N.; Lejeune, Benjamin; Lepoint, Gilles; Amaral, Rodrigo Gonçalves [UNESP]; Sabino, Gabriel Pavan; Araújo, Márcio Silva [UNESP]; Rezende, Gabriela Cabral; Brotcorne, Fany; Culot, Laurence [UNESP] (Wiley, 2025)
Given the cryptic and elusive nature of prey consumption, quantifying its contribution to the diet of free-ranging primates using behavioral methods is challenging. In this context, the use of carbon and nitrogen-stable isotopes represents a promising alternative approach. Here, we used stable isotope analysis to estimate the proportion of arthropods and fruits in the diet of black lion tamarins (Leontopithecus chrysopygus), an endangered primate endemic to the Brazilian Atlantic Forest. To do so, we ran stable isotope mixing models using isotopic data from hair samples of black lion tamarins living in six forest fragments showing different levels of habitat quality. Furthermore, we ran linear mixed models to assess the influence of habitat quality—fruit productivity (estimated by tree total basal area) and arthropod biomass – and individual characteristics (sex and body mass) on tamarins' δ15N values (a proxy for trophic position). Our results revealed that arthropods contributed more to black lion tamarins' diet than reported in previous behavioral studies, suggesting that behavioral observations may considerably underestimate the importance of arthropodivory in the diet of arboreal primates. The degree of arthropodivory and frugivory was similar within groups, in line with the strong group cohesion and synchronization of feeding behaviors of this species and supporting the role of site-specific habitat characteristics on dietary choice. Arthropod consumption was higher in areas with lower fruit productivity and did not increase when arthropod biomass increased, suggesting that fruits represent a limiting but preferred resource for this species. These results demonstrate the dietary plasticity of black lion tamarins in areas of lower forest quality, where they manage to compensate low fruit productivity by shifting to a diet richer in arthropods. Considering that this species occurs within a highly fragmented landscape, preserving and protecting small forest patches remains crucial for the conservation of this species.
Keywords: diet; habitat fragmentation; Leontopithecus chrysopygus; primate conservation; trophic ecology